Further Analysis of the Short-Run Consumption Function with Emphasis on the Role of Liquid Assets - Zellner, A.; Huang, D. S.; Chau, L. C. (Econometrica, 1965)
IN THIS paper we report the results of additional experiments with the short-run consumption function. In particular, in Section 2 we take up the problem of isolating expectation, inertia, and habit persistence effects and then go on in Section 3 to the problem of interpreting and estimating a real balance effect. As will be seen, the present work involves nonlinear relationships which have been estimated employing nonlinear techniques. Further, the problem of autocorrelation in distributed lag schemes is dealt with in a manner suggested by Fuller and Martin (1961). Aside from illustrating approaches to these methodological problems, the present study yields results on the role of liquid assets in determining consumption expenditures which, we believe, are of consequence with respect to establishing a direct influence of monetary variables on an expenditure relationship. This and other aspects of our study are discussed and summarized in Section 4.